Surgical treatment of severe pancreatic fistula after pancreaticoduodenectomy by wirsungostomy and repeat pancreatico-jejunal anastomosis - Paye, François; Lupinacci, Renato M.; Kraemer, Aurore; Lescot, Thomas; Chafaï, Najim; Tiret, Emmanuel; Balladur, Pierre (The American journal of surgery, 2013)
After pancreaticoduodenectomy, severe pancreatic fistula may require salvage relaparotomy in patients with largely disrupted pancreaticojejunal anastomosis. Completion pancreatectomy remains the gold standard but yields high mortality and severe long-term repercussions. The authors report the results of a pancreas-preserving strategy used in this life-threatening condition. Two hundred fifty-four pancreaticoduodenectomies with pancreaticojejunal anastomosis were performed between 2005 and 2011; 21 patients underwent salvage relaparotomy for grade C pancreatic fistula. Largely dehiscent pancreaticojejunal anastomoses were dismantled in 16 patients. Four patients underwent completion pancreatectomy, whereas in 12 patients detailed here, the remaining pancreas was preserved and drained by wirsungostomy with exteriorization or closure of the jejunal stump. Repeat pancreaticojejunal anastomosis was later planned to preserve pancreatic function. One patient died of recurrent hemorrhage on day 1 after wirsungostomy (8.3%). All but 1 survivor developed postoperative complications, and 3 needed reoperation before hospital discharge. The median hospital stay was 62 days (range, 29 to 156 days). After a median delay of 130 days (range, 91 to 240 days) from salvage relaparotomy, repeat pancreaticojejunostomy was attempted in 10 patients and was successful in 9 (1 completion pancreatectomy was performed). One patient died postoperatively (10%). Long-term endocrine function was unaltered in 66% of patients who benefited from this conservative strategy. This pancreas-preserving strategy yielded a whole mortality rate of 17% for largely disrupted pancreaticojejunal anastomosis requiring salvage relaparotomy. It compares favorably with systematic completion pancreatectomy and achieved preservation of remnant pancreatic function in 75% of patients.